A comparison of three quality of life instruments in subjects with angina pectoris: the sickness impact profile, the Nottingham health Profile, and the quality of well being scale - Visser, M.C.; Fletcher, A.E.; Parr, G.; Simpson, A.; Bulpitt, C.J. (Journal of clinical epidemiology, 1994)
Three instruments for the assessment of quality of life, the Quality of Well Being index (QWB), the Nottingham Health Profile (NHP) and the Sickness Impact Profile (SIP) were assessed in 59 patients with angina pectoris. The NHP showed increased statistically significant impairment with higher New York Heart Association (NYHA) class in 4 out of 6 subscales but not in single responses to questions on daily life. In the SIP 9 out of 11 dimensions increased with NYHA grade as did the physical and psychooocial subscores and the total score. There were statistically significant increases in six of the eleven dimensions. In the QWB an increase was observed only for two out of four categories employed in this instrument. The QWB was the most difficult to administer and thought likely to be insensitive to changes in anginal pain. There was a high level of agreement in similar dimensions of NHP and SIP. A psychological distress score was evaluated using the Symptom Rating Test and correlated with all summary dimensions of both instruments. The coefficients of variation were lower in SIP than in NHP categories. In conclusion quality of life instruments like NHP and SIP may be able to identify treatment effects in angina patients and so yield a useful addition to the traditional measures employed for the assessment of their condition.